Gingival Fenestration: A Multidisciplinary Approach - Pradhan, Ameena; Aryal, Shreeya; Joshi, Neera; Shrestha, Shilu (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Gingival fenestration is rarely encountered clinical situation causing problems like root sensitivity, root caries and aesthetic problem. Although rare, this situation can be difficult to manage and needs multidisciplinary approach. This case report describes management of gingival fenestration defect with root exposure and endodontic lesion in upper left lateral incisor using multidisciplinary approach. Endodontic treatment followed by double papilla flap technique as coverage of gingival fenestration and finally crown was prosthetically rehabilitated. The result of this case with double papilla graft technique demonstrated satisfactory healing of the gingival fenestration defect with excellent colour and texture match with the surrounding tissues.